Perspectives for the high field approach in fusion research and advances within the Ignitor Program. (15th April 2015) - Coppi, B.; Airoldi, A.; Albanese, R.; Ambrosino, G.; Belforte, G.; Boggio-Sella, E.; Cardinali, A.; Cenacchi, G.; Conti, F.; Costa, E.; D'Amico, A.; Detragiache, P.; et al.
Abstract: The Ignitor Program maintains the objective of approaching D–T ignition conditions by incorporating systematical advances made with relevant high field magnet technology and with experiments on high density well confined plasmas in the present machine design. An additional objective is that of charting the development of the high field line of experiments that goes from the Alcator machine to the ignitor device. The rationale for this class of experiments, aimed at producing poloidal fields with the highest possible values (compatible with proven safety factors of known plasma instabilities) is given. On the basis of the favourable properties of high density plasmas produced systematically by this line of machines, the envisioned future for the line, based on novel high field superconducting magnets, includes the possibility of investigating more advanced fusion burn conditions than those of the D–T plasmas for which Ignitor is designed. Considering that a detailed machine design has been carried out (Coppi et al 2013 Nucl. Fusion 53 104013 ), the advances made in different areas of the physics and technology that are relevant to the Ignitor project are reported. These are included within the following sections of the present paper: main components issues, assembly and welding procedures; robotics criteria; non-linear feedback control; simulations with three-dimensional structures and disruption studies; ICRH and dedicated diagnostics systems; anomalous transport processes including self-organization for fusion burning regimes and the zero-dimensional model; tridimensional structures of the thermonuclear instability and control provisions; superconducting components of the present machine; envisioned experiments with high field superconducting magnets.